2010
DOI: 10.1371/journal.pbio.1000354
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Fe–S Cluster Assembly and tRNA Thiolation Mediated by IscS Protein–Protein Interactions

Abstract: Crystal structures reveal how distinct sites on the cysteine desulfurase IscS bind two different sulfur-acceptor proteins, IscU and TusA, to transfer sulfur atoms for iron-sulfur cluster biosynthesis and tRNA thiolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
387
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(417 citation statements)
references
References 66 publications
28
387
1
1
Order By: Relevance
“…S7) to estimate the mass of the complex in solution. The size determined (102 kDa) is in agreement with the ðIscUÞ 2 ∶ðIscSÞ 2 stoichiometry of the complex and the X-ray structure, which shows one IscU bound to each IscS subunit (8). Given the size of the complex, backbone signals from IscU residues in the binding site with IscS are expected to be exceedingly broad and not visible in the 1 H-15 N spectrum.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…S7) to estimate the mass of the complex in solution. The size determined (102 kDa) is in agreement with the ðIscUÞ 2 ∶ðIscSÞ 2 stoichiometry of the complex and the X-ray structure, which shows one IscU bound to each IscS subunit (8). Given the size of the complex, backbone signals from IscU residues in the binding site with IscS are expected to be exceedingly broad and not visible in the 1 H-15 N spectrum.…”
Section: Resultssupporting
confidence: 77%
“…The solution studies reported here suggest that the differential affinities of the D and S states of IscU play an important role in efficient iron-sulfur cluster assembly. Our finding that apoIscU is largely disordered when bound to IscS differs from recent reports of X-ray (8), NMR (9), and small angle X-ray scattering (8,10) investigations that found the IscU component to be structured within the IscU:IscS complex.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Sous cette forme, le soufre est activé, mobilisable et non toxique. IscS s'associe avec IscU (iron-sulfur cluster scaffold), une protéine servant de plate-forme d'assemblage pour les centres Fe-S [15,16]. De façon remarquable, la formation et la stabilisation transitoire de ces centres impliquent trois résidus Cys de IscU, mais aussi le résidu Cys catalytique de IscS [17].…”
Section: Biogenèse Des Centres Fe-sunclassified